Portfolio management in new product development lessons from the leaders-II - Cooper, Robert G. (Research management (Now: research technology management))
Robert G. Cooper, Scott J. Edgett and Elko J. Kleinschmidt examine how leading firms attempt to link their R&D portfolios to the strategies of their businesses.